(untitled) (Medicine Today, 2020)
Introduction:Smoking is most common in East Asia, where two thirds of all adult males smoke tobacco; cigarette smoking is by far the most common. Smoking is the primary cause of chronic obstructive lung disease, chronic bronchitis and other respiratory symptoms. Many studies have shown significant changes of Forced Expiratory Flow (FEF) as FEF 25, FEF 50 and FEF 75 (L/sec) in adult male smokers. Its objective is to assess the change of FEF 25, FEF 50 and FEF 75 (L/sec) in adult male smokers. Materials and Methods: This cross-sectional comparative study was carried out in the Department of Physiology, Dhaka Medical College, Dhaka during the period of July, 2007 to June, 2008. In the present study 30 adult male smokers consuming cigarettes for more than 5 years selected as study group (Group-B) and were matched with 30 adult males who were non-smokers considered as control group (Group-A) for comparison. FEF 25, FEF 50 and FEF 75 (L/sec) were estimated in both Groups. Analysis of data was done with the help of computer by SPSS 12.0 programmer and significant tests were done by unpaired Student’s “t” test. Results: There were statistically significant differences of FEF25, FEF50 and FEF75 (L/sec) in group A vs. group B. Conclusion: From the statistical analysis of the results obtained in the present study and their comparison with those of published reports, it may be concluded that smoking causes significant change of FEF 25, FEF 50 and FEF 75 (L/sec) among the smokers that could be useful in early diagnosis of peripheral airway obstruction. Medicine Today 2020 Vol.32(2): 81-84